1994
DOI: 10.1128/aem.60.6.1711-1718.1994
|View full text |Cite
|
Sign up to set email alerts
|

Role of mycelium and extracellular protein in the biodegradation of 2,4,6-trichlorophenol by Phanerochaete chrysosporium

Abstract: The biodegradation of 2,4,6-trichlorophenol (2,4,6-TCP) by Phanerochaete chrysosporium was studied in batch systems. In experiments with mycelial suspension, the degradation of 2,4,6-TCP was found to occur in the absence of ligninase. Chloride ion was recovered in nearly stoichiometric amounts at the end of the process. The microorganism did not retain its degradation ability for more than 6 days under substrate-deficient conditions. Neither the mycelium nor the extracellular protein alone could degrade 2,4,6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…The mycelium left in the bottles was washed, resuspended, and centrifuged three times using a wash solution having the same composition of the growth medium but containing no glucose and nitrate in order to prevent fungal growth. 2 The washed mycelium was transferred to a single container to which an aliquot of the 2,4,6-TCP stock solution was added. After adjusting the pH, the suspension was brought up to 500 mL with wash solution and transferred to four replicate 250-mL Erlenmeyer flasks (100 mL/flask).…”
Section: Experiments With Washed Myceliummentioning
confidence: 99%
See 1 more Smart Citation
“…The mycelium left in the bottles was washed, resuspended, and centrifuged three times using a wash solution having the same composition of the growth medium but containing no glucose and nitrate in order to prevent fungal growth. 2 The washed mycelium was transferred to a single container to which an aliquot of the 2,4,6-TCP stock solution was added. After adjusting the pH, the suspension was brought up to 500 mL with wash solution and transferred to four replicate 250-mL Erlenmeyer flasks (100 mL/flask).…”
Section: Experiments With Washed Myceliummentioning
confidence: 99%
“…Armenante et a1 . 2 have recently shown that the degradation of 2,4,6-TCP by P. chrysosporium is a process that requires the simultaneous presence of both the mycelium and the extracellular enzyme system released by the mycelium to initiate degradation. These investigators have also shown that the rate-limiting step in the process is the concentration of extracellular protein and that the concentration of mycelial biomass does not affect the rate of degradation, although the presence of some biomass is necessary for degradation to occur.…”
Section: Proposed Reaction Scheme and Mathematical Modelmentioning
confidence: 99%
“…Extracellular lignin-degrading enzymes such as lignin peroxidase (LiP) and manganese peroxidase (MnP) produced by white-rot basidiomycete fungi have been reported to be involved in transformation of various CDDs (and various chlorophenols etc.) (Armenante et al 1994;Bumpus et al 1985;Joshi and Gold 1993;Joshi and Gold 1994;Reddy and Gold 2000;Takada et al 1996;Valli et al 1992). Through various metabolic pathways, the white-rot basidiomycete fungi convert the chlorinated aromatic compounds to CO 2 and H 2 O.…”
Section: Introductionmentioning
confidence: 99%
“…The biodegradation of low-chlorinated phenols has been studied in both aerobic and anaerobic systems (Steiert et al 1987;Larsson et al 1988;Larsson and Lemkemeier 1989;Kramer and Kory 1992;Kafkewitz et al 1992;Kiyohara et Armenante et al 1994). Considerable efforts have also been made to develop biological treatments for some of these chemicals (Balfanz and Rehm 1991 ;Armenante et al 1992 ;Menke and Rehm 1992 ;Armenante et al 1993).…”
Section: Introductionmentioning
confidence: 99%